2018
DOI: 10.1371/journal.pone.0209230
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylceramide acyl chain length is sensed by the glycolipid transfer protein

Abstract: The glycolipid transfer protein, GLTP, can be found in the cytoplasm, and it has a FFAT-like motif (two phenylalanines in an acidic tract) that targets it to the endoplasmic reticulum (ER). We have previously shown that GLTP can bind to a transmembrane ER protein, vesicle-associated membrane protein-associated protein A (VAP-A), which is involved in a wide range of ER functions. We have addressed the mechanisms that might regulate the association between GLTP and the VAP proteins by studying the capacity of GL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…LTPs have been discovered and studied for more than 40 years, yet few studies have explored how their activity depends on the nature of the lipid acyl chains. A few kinetic studies have shown that a nonspecific-LTP transfers shorter PC more easily than long PC [ 50 ], that a glycolipid transfer protein (GLTP) preferentially transports short glucosylceramides [ 51 ] and that the ceramide transfer protein (CERT) is active with ceramide species whose length does not exceed the size of its binding pocket [ 52 , 53 ]. Moreover, the link between the activity of LTPs and their affinity for lipid ligands remained largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…LTPs have been discovered and studied for more than 40 years, yet few studies have explored how their activity depends on the nature of the lipid acyl chains. A few kinetic studies have shown that a nonspecific-LTP transfers shorter PC more easily than long PC [ 50 ], that a glycolipid transfer protein (GLTP) preferentially transports short glucosylceramides [ 51 ] and that the ceramide transfer protein (CERT) is active with ceramide species whose length does not exceed the size of its binding pocket [ 52 , 53 ]. Moreover, the link between the activity of LTPs and their affinity for lipid ligands remained largely obscure.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, accumulation of short-chain at the expenses of long-chain SL could alter the structural order of membrane lipid bilayers, modify membrane curvature and disrupt membrane fluidity (Niemelä et al, 2006;Ben-David and Futerman, 2010;Mencarelli and Martinez-Martinez, 2013). A switch from long-to short-chain molecules could also interfere with lipid-protein interactions at the plasma membrane level and affect signalling responses involved, for example, in lipid and protein trafficking and degradation and in cell death pathways (Sillence et al, 2002;Kroesen et al, 2003;Koivusalo et al, 2007;Sassa et al, 2012;Ali et al, 2013;Backman et al, 2018). and GBA-mutant mice (Sun et al, 2005;Mazzulli et al, 2011;Sardi et al, 2011;Xu et al, 2011;Cleeter et al, 2013;Schöndorf et al, 2014;Aflaki et al, 2016;Migdalska-Richards et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of FAPP2 disrupts GlcCer transport from cis- to trans-Golgi, resulting in a disturbed synthesis of complex glycosphingolipids ( D'Angelo et al, 2007 ; D'Angelo et al, 2013 ; Halter et al, 2007 ). How FAPP2 aids in the transport of GlcCer from the cis to the trans-Golgi is not yet fully understood, but may involve ER–Golgi contact sites: FAPP2 has a putative FFAT motif ( Backman et al, 2018 ) and has been suggested to transfer GlcCer retrogradely to the ER, where GlcCer translocates into the lumen. From the ER lumen, GlcCer could be anterogradely transported to the trans-Golgi for further glycosylation into complex glycosphingolipids ( Halter et al, 2007 ).…”
Section: Er-mediated Regulation Of the Golgimentioning
confidence: 99%